Proton minibeam radiotherapy: a review - Yang, Feng; Wu, Junxiang; Orlandini, Lucia Clara; Li, Heng; Wang, Xianliang (Frontiers in Oncology, 2025)
Radiotherapy plays a crucial role in cancer treatment. Spatially fractionated radiotherapy (SFRT) has garnered significant interest as a therapeutic strategy that delivers alternating regions of high and low radiation doses, thereby optimizing the therapeutic ratio by minimizing damage to adjacent normal tissues while achieving tumoricidal effects. Proton minibeam radiotherapy (pMBRT), a cutting-edge iteration within the SFRT paradigm, has attracted considerable attention owing to its purported benefits in dose distribution optimization, enhanced tumor control, and superior preservation of normal tissue. This manuscript presents an extensive evaluation of different applications of pMBRT, with a focus on the outcomes observed in preclinical research studies. Additionally, we explored the challenges faced in translating pMBRT from research to clinical practice, while also highlighting the significant potential this technique holds for the future of cancer treatment.